2022
DOI: 10.1186/s41938-021-00499-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of endophytic Bacillus and arbuscular mycorrhiza fungi (AMF) against Fusarium wilt of tomato caused by Fusarium oxysporum f. sp. lycopersici

Abstract: Background Fusarium wilt of tomato caused by Fusarium oxysporum f. sp. lycopersici (FOL) is a serious disease that causes significant economic losses in tomato production. Seventeen endophytic Bacillus isolates from tomato roots of Meghalaya were tested for antagonistic and plant growth promotion activities. Dominating arbuscular mycorrhiza fungi (AMF) spores were isolated from the rhizosphere soils of tomato grown in Meghalaya. The effect of different combinations of AMF and endophytic Bacillu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(17 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…A similar feature of these symbioses is the evidence of mutual recognition between terrestrial plants and bacterial or fungal microorganisms prior to host-regulated microbial entry [42]. Thus, these symbionts modify the resistance of plants to disease, reduce the impact of pathogens and improve the overall integrity of crops [43,44]. They also act as indirect support for plant growth and development [45,46], by changing the phosphorus mechanism and partially the replacing use of fertilizers.…”
Section: Discussionmentioning
confidence: 97%
“…A similar feature of these symbioses is the evidence of mutual recognition between terrestrial plants and bacterial or fungal microorganisms prior to host-regulated microbial entry [42]. Thus, these symbionts modify the resistance of plants to disease, reduce the impact of pathogens and improve the overall integrity of crops [43,44]. They also act as indirect support for plant growth and development [45,46], by changing the phosphorus mechanism and partially the replacing use of fertilizers.…”
Section: Discussionmentioning
confidence: 97%
“…Arbuscular mycorrhizal fungi (AMF), generally forming a symbiotic relationship with approximately 80% of terrestrial plants, can play a crucial role in the plants to face many biotic and abiotic stresses, such as pests, plant pathogens, drought, waterlogging, low temperature, and salinity ( Begum et al., 2019 ; Devi et al., 2022 ; Sivaprakasam Padmanaban et al., 2022 ; Zhang et al., 2022 ). Previous studies demonstrated the function of AMF in controlling anthracnose disease in many herbaceous plants such as Fragaria×ananassa Duch.…”
Section: Introductionmentioning
confidence: 99%
“…Bacterial isolates were spot inoculated onto 2% (w/v) NaCl pectin (10 g/L) agar plates ( Devi et al, 2022 ) and incubated at 28 °C for 7 days. After incubation, the plates were stained with 1% iodine solution for 15 min, then washed with water.…”
Section: Methodsmentioning
confidence: 99%